Regulamentação da denominação de origem protegida de queijos da Espanha e sua aplicação em queijo de coalho - Abrantes, Maria Rociene (Universidade Federal Rural do Semi-Árido, 2016)
This study aimed to analyse certification of origin as a form to add value to artisanal cheeses, such as coalho cheese, in Brazil and Spain. For such, we analysed the formation of prices, market structure and production systems of palmero cheese, which has Protected Designation of Origin (PDO) in the Canary Islands, Spain. The study was based on interviews with PDO and non-PDO producers concerning the production systems, social issues, markets and marketing channels. In addition, we evaluated 25 PDO cheese regulations from Spain and investigated its resemblance to coalho cheese. In Brazil, we evaluated the quality of the artisanal and industrial coalho cheese marketed in the Brazilian semiarid region. For this purpose, 138 coalho cheese samples were analysed as to their physical-chemical parameters (acidity, ash, fat, moisture and pH), colour, texture; microbiological parameters (coliforms at 35°C and 45°C, coagulase positive Staphylococcus, mould and yeast and Salmonella spp.); the type of production and conservation; the presence of enterotoxigenic genes; and the antimicrobial resistance profile of Staphylococcus aureus. We observed that the PDO palmero cheese obtained higher market price and the highest price was through the “direct to the consumer” sales channel. Furthermore, we found that both PDO and non-PDO producers were concerned with the quality of the palmero cheese and relevance of the PDO label. As to the analysis of the regulations, PDO and the other variables were classified into four different groups and there was correlation between them. Group one, had fewer PDO regulation and similarities in the historical, natural environment, agriculture and responsible authority aspects, and less so in the economic importance aspect. Group two, regulations were focused on infractions, penalties and fines, and little on the quality manual. Group three tended to have similar values for most variables. Moreover, group 4 showed similarity in the quality manual and less concern given to infractions, penalties and fines. We could observe that the coalho cheese presented some of the variables found in PDO cheeses such as reputation, cultural, historical, artisanal, economic, developmental and quality characteristics. Regarding the quality of the coalho cheese, the physical-chemical analysis, colour and texture showed statistical difference only for ashes, for the type of production. The microbiological analysis presented significant difference in production, higher amounts of coliforms in artisanal samples and as to the type of conservation, higher amounts for coliforms, yeasts, and moulds in the artisanal samples without refrigeration. Furthermore, we found the presence of Salmonella spp. in 2.17% of samples, that is, one artisanal sample and two industrial samples. As for coliforms at 45°C, we found that 25.36 and 3.95% of artisanal and industrial samples, respectively, were in disagreement with the legislation and concerning Staphylococcus positive coagulase all samples were non-compliant. In total, 67 samples were confirmed by amplification of the 16S rRNA gene for S. aureus. Of these, 12 (17.9%) amplified toxin genes. The isolates presented greater resistance to the antibiotics penicillin G, oxacillin and tetracycline. Thus, the origin certification is an important tool to enhance the value of artisanal cheeses and can be used by coalho cheese; however, producers first need to improve in quality and standardization of manufacturing
Normalisation of the protected origin denomination of cheeses from Spain and its application to coalho cheese
Keywords: Denominação de origem protegida; Queijo de coalho; Queijo artesanal; Protected designation of origin; Coalho cheese; Artisanal cheese; CIENCIAS AGRARIAS::MEDICINA VETERINARIA